Rancang Model Ontologi untuk Representasi Pengetahuan Rumah Tradisional di Indonesia - Pramesti, Kadek Diah; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 3 (2024): JELIKU Volume 12 No 3, February 2024DO - 10.24843/JLK.2023.v12.i03.p03, 2023)
Indonesia is famous for its diversity from ethnicity, religion, culture, customs, to traditional buildings or commonly called traditional houses. There are many traditional houses in Indonesia. Each region or place has its own traditional house or building. To preserve this traditional house, a model such as Ontology is needed. The ontology knowledge base is an appropriate method used to represent information. In this project, the ontology model was built using the Protégé ontology development tool. We use the method of METHONTOLOGY in the development of the ontology model where this method describes each step-in detail. The ontology model built has 9 classes, 4 object properties, 1 data properties, and 80 individuals. The testing process in the development of the ontology model by performing SPARQL queries.